Manajemen Pembelajaran Berbasis Hybrid Learning Pasca Pandemi di MTs Negeri 01 Kepahiang - Aziz, Toher; Wanto, Der; Kusen, Kusen (El-Idare, 2023)
Hybrid learning is a combinetion offline learning media and online. There are several platforms that are considered popular in online learning activities such as Zoom meetings, Google Classroom, Google Forms, Whatsapp, Youtube, e-learning, learning strategies by combining offline and online media. this is often also referred to as the Blended Learning learning method, there are also those who term it the Hybrid Learning method, hybrid learning that has been used by teachers at MTsN 01 Kepahiang so that it can run optimally and according to what is expected. The subjects of this study were all 40 teachers at MTsN 01 Kepahiang who were then classified based on the research problem of teachers namely those carrying out hybrid/blended learning 16 homeroom teachers, 2 teachers using google classroom, 3 mathematics teachers using the Alef application, 40 subject teachers who carried out the exam, 3 people used YouTube videos. The results of the study that based on the results of interviews and observations it can be concluded that in the process of carrying out post-pandemic Hybrid learning it has been carried out properly and using the available devices and applications. It is considered the easiest and cheapest to use and can be applied as a whole by teachers in conveying material or assignments as well as students in receiving and absorbing material and as a medium of communication that is flexible in connecting.